The effects of environmental stressors in intensive care unit on anxiety and depression - (:unkn) unknown (WILEY, 2022)
Background Physical and emotional conditions of patients treated in an intensive care unit (ICU) may be adversely affected by environmental stressors. Aims and objectives The aim of this study was to investigate the relationship between patients' anxiety and depression levels and environmental stressors in the ICU. Design This was a descriptive cross-sectional study. Methods The study was conducted between June 2018 and April 2019 with 150 patients treated in the ICUs of a training and research hospital. Patient information form and ICU environmental stressors and hospital anxiety and depression scales were used for data collection. Descriptive statistics,t-test, one-way analysis of variance, and Pearson's correlation coefficient were used to evaluate the data. Results The mean hospital anxiety score of the patients in ICUs was 11.1 +/- 2.7, and 77.3% of patients were at risk for anxiety (10-point cut-off). The mean hospital depression score was 10.6 +/- 3.3, and 94% of patients were at risk for depression (7-point cut-off). The mean score of environmental stressors was 123.9 +/- 13.1. A moderate positive correlation between hospital anxiety and hospital depression (r = .63,P < .001) and a weak negative correlation between environmental stressors and hospital anxiety (r = -.24,P= .003) were found. However, no significant correlation between environmental stressors and hospital depression was found (r = -.13,P= .12). Conclusion According to this study, the environmental stressors in the ICU were high, and the patients were at risk of anxiety and depression. The depression levels of the patients increased along with their anxiety levels. As environmental stressors increased, hospital anxiety levels of the patients decreased. However, there was no significant relationship between environmental stressors and patients'hospital depression levels. Relevance to clinical practice Environmental stressors in ICUs are high, and the patients in the ICUs are at risk of anxiety and depression.
Keywords: anxiety; depression; environmental stressors; intensive care; nursing; PERCEPTION; PATIENT; NURSES